Cultures of high-frequency trading: mapping the landscape of algorithmic developments in contemporary financial markets. Issue 2 (2nd April 2016) - Lange, Ann-Christina; Lenglet, Marc; Seyfert, Robert
Abstract: As part of ongoing work to lay a foundation for social studies of high-frequency trading (HFT), this paper introduces the culture(s) of HFT as a sociological problem relating to knowledge and practice. HFT is often discussed as a purely technological development, where all that matters is the speed of allocating, processing and transmitting data. Indeed, the speed at which trades are executed and data transmitted is accelerating, and it is fair to say that algorithms are now the primary interacting agents operating in the financial markets. However, we contend that HFT is first and foremost a cultural phenomenon. More specifically, both individuals and collective agents – such as algorithms – might be considered cultural entities, charged with very different ways of processing information, making sense of it and turning it into knowledge and practice. This raises issues relating to situated knowledge, distributed cognition and action, the assignment of responsibility when regulating high-speed algorithms, their history, organizational structure and, perhaps more fundamentally, their representation.